Impact of the Digital Transformation of Society on the Determination of Optimal Punishment Models to Counter Crime - Krainova, Nadezhda; Gaag, Irina; Poshivailova, Anna (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
This study aims to define the essence of punishment from both retrospective and prospective perspectives, particularly in the context of the digital transformation of society. The study draws on qualitative methods, including a comprehensive analysis of contemporary scientific literature and expert interviews, to examine the evolving nature of punishment. The analysis is grounded in the views of prominent researchers and theorists, allowing the authors to develop their theoretical provisions regarding the moral nature of punishment. These provisions emphasize the importance of maintaining the human element in the penal system, arguing that the moral judgment inherent in punishment should not be entirely entrusted to digital instruments or artificial intelligence. Instead, the study advocates for a balanced approach that recognizes the potential of digital tools to enhance efficiency while cautioning against their excessive use in penological practice. Furthermore, the study highlights probation techniques as a key means of individualized crime prevention, suggesting that these techniques should remain central to the penal system in an era of digital transformation. By focusing on the human capacity for moral judgment and individualized prevention, the study proposes that the role of digital tools should be supplementary rather than central. In conclusion, the study recommends that legislators and practitioners prioritize the preservation of human judgment in punishment practices, using digital tools cautiously and ensuring that they do not undermine the moral and individualized aspects of justice. The findings suggest a need for further research into the ethical implications of digitalization in criminal justice, particularly regarding the balance between human and digital roles in punishment.